Analisis Tingkat Kesehatan Bank Mandiri Syariah Dengan Metode Risk Profile, Good Corporate Governace, Earnings and Capital - Anik Anik; Suhesti Ningsih (Jurnal Ilmiah Ekonomi Islam, 2020)
The purpose of this research is to see the soundness level of Bank Syariah Mandiri with the method of Risk Profile, Good Corporate Governance, Earnings and Capital. The research method uses quantitative methods. Production factors in the RGEC method are the risk profile using credit risk (NPF), liquidity risk (FDR), income (ROA, ROE and BOPO) and capital (CAR). On the results of Good Corporate Governance using data processed and obtained from PT. Bank Syariah Mandiri. The object of this research is PT. Bank Syariah Mandiri. The sampling technique in this study using purposive sampling. This research period is 2013-2017. The data analysis technique used in this research is quantitative descriptive and using the RGEC method (Risk Profile, Good Corporate Governance, Earnings and Car), as for the benchmarks to determine the soundness level of a bank after each examination, namely by determining the results of the study classified into the bank's health rating. The results showed that the health of PT. Bank Syariah Mandiri which uses the Risk Profile approach, Good Corporate Governance, Earnings, and Capital as a whole can be said that Bank Syariah Mandiri is a fairly healthy bank.